We have the next polynomial equation
![\mleft(x^2-9\mright)\mleft(x^2+4\mright)=0](https://img.qammunity.org/2023/formulas/mathematics/college/iitd29xureto9o6wasrl5u1r4wjc0o9dii.png)
First we will solve because if this binomial is zero all the polynomial expression is zero
![\mleft(x^2-9\mright)=0](https://img.qammunity.org/2023/formulas/mathematics/college/aavklxetjj4tpxxr6pjhr3jw2o8xse05ue.png)
![\begin{gathered} x^2=9 \\ x=\pm\sqrt[]{9} \\ x=\pm3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/qsycdj8vvnlx70z4a626ehbzrrb2pbdpn4.png)
the first two solutions are x=3, x=-3
For the second binomial
![(x^2+4)=0](https://img.qammunity.org/2023/formulas/mathematics/college/k9h32inqfd58a9umyjgqif74quk9kq3gi5.png)
![\begin{gathered} x^2=-4 \\ x=\pm\sqrt[]{-4} \\ x\pm2i \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vhlaizrgoit8bnx4rbz3xds8f8pj6u8o3l.png)
the other solutions are x=2i, x=-2i
The solutions of the polynomial equation are
x=3
x=-3
x=2i
x=-2i